Effect of Implementation of Attention Relevance Confidence Satisfaction Learning Model on Interests and Learning Outcomes of Students on Quadrilateral Materials - Nadya Alvi Rahma (UMSU, 2023)
This research is motivated by several factors including the lack of interest in learning of students as evidenced by the lack of participation of students in learning activities, the delay of students in submitting assignments and the lack of attention of students during learning activities takes place. The purpose of this study was to determine the effect of applying the Attention Relevance Confidence Satisfaction (ARCS) learning model on students' learning interest. This study uses a quantitative approach with a quasi-experimental design. The population of this study were all class VII students of SMPN 2 Ngantru Tulungagung for the 2021/2022 academic year. Sampling was done by purposive sampling. The results of this study indicate that there is an effect of the application of ARCS learning model on the learning interest of class VII students at SMPN 2 Ngantru Tulungagung on the Quadrilateral Materials